Assessing eligibility for differentiated service delivery, HIV services utilization and virologic outcomes of adult HIV-infected patients in Sierra Leone: a pre-implementation analysis. Issue 1 (1st January 2021) - Lakoh, Sulaiman; Jiba, Darlinda F.; Vandy, Alren O.; Poveda, Eva; Adekanmbi, Olukemi; Murray, Mariama J.S.; Deen, Gibrilla F.; Sahr, Foday; Hoffmann, Christopher J.; Jacobson, Jeffrey M.; Salata, Robert A.; Yendewa, George A.
ABSTRACT: Background: There are limited data to help guide implementation of differentiated HIV service delivery (DSD) in resource-limited settings in sub-Saharan Africa. Objectives: This pre-implementation study sought to assess the proportion of patients eligible for DSD and HIV services utilization, as well as risk factor analysis of virologic failure in Sierra Leone. Methods: We conducted a retrospective study of adult HIV-infected patients aged 18 years and older receiving care at the largest HIV treatment center in Sierra Leone 2019–2020. Multiple logistic regression was used to identify predictors of virologic failure. Results: Of 586 unique patients reviewed, 210 (35.8%) qualified as 'stable' for antiretroviral therapy (ART) delivery. There was high utilization of certain HIV service programs (e.g. HIV status disclosure to partners (83%) and treatment 'buddy' program participation (62.8%)), while other service programs (e.g. partner testing and community HIV support group participation) had low utilization (<50%). Of 429 patients with available viral load, 277 (64.6%) were virologically suppressed. In the multivariate logistic regression analysis of risk factors of virologic failure, CD4 < 350 cells/mm 3 (p = 0.009), atazanavir-based ART (p = 0.032), once monthly versus once two- or three-monthly ART dispensing (p = 0.028), history of ART switching (p = 0.02), poor adherence (p = 0.001) and not having received adherence support (p < 0.001) were independent predictors of virologic failure. Conclusion: Approximately one in three HIV-infected patients on ART were eligible for DSD. We identified gaps in HIV care (i.e. low partner testing, treatment 'buddy', program participation and a substantially high rate of virologic failure) that need to be addressed in preparation for full implementation of DSD in Sierra Leone.